Metabolic syndrome and cardiovascular risk among patients with schizophrenia receiving antipsychotics in Malaysia - Said, Mas Ayu; Sulaiman, Ahmad Hatim; Habil, Mohd Hussain; Das, Srijit; Bakar, Abdul Kadir Abu; Yusoff, Rosliwati Md; Loo, Tsui Huei; Bakar, Shamshunnisah Abu (Singapore Medical Association, 2012)
INTRODUCTION This study aimed to determine the prevalence of metabolic syndrome and risk of coronary heart disease (CHD) in patients with schizophrenia receiving antipsychotics in Malaysia. METHODS This cross-sectional study, conducted at multiple centres, involved 270 patients who fulfilled the Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV-TR diagnostic criteria for schizophrenia, were on antipsychotic medications for at least one year, and were screened for metabolic syndrome. Patients receiving mood stabilisers were excluded. Metabolic syndrome was defined according to the National Cholesterol Education Program ATP III criteria modified for Asian waist circumference. Risk for cardiovascular disease was assessed by using Framingham function (all ten-year CHD events). RESULTS The prevalence of metabolic syndrome was 46.7 (126/270). Among all the antipsychotics used, atypical antipsychotics (monotherapy) were most commonly used in both the metabolic and non-metabolic syndrome groups (50.8 vs. 58.3). The ten-year risk for CHD was significantly higher in patients with metabolic syndrome. The proportion of patients with high/very high risk for CHD (Framingham >= 10) was greater in patients with metabolic syndrome than in those with non-metabolic syndrome (31.5 vs. 11.0, odds ratio 3.9, 95 confidence interval 2.0-7.6; p < 0.001). The mean body mass index was higher in patients with metabolic syndrome than in those without (29.4 +/- 5.1 kg/m(2) vs. 25.0 +/- 5.6 kg/m(2); p < 0.001). CONCLUSION Patients with schizophrenia receiving antipsychotics in Malaysia have a very high incidence of metabolic syndrome and increased cardiovascular risk. Urgent interventions are needed to combat these problems in patients.